Observation and modelling of wave nonlinearities and infragravity waves in the nearshore - Rocha, Mariana Vieira Lima Matias da (2017)
Wave nonlinearities have long been recognised as being among the main drivers of sediment transport in the coastal zone. However, there are still signi cant errors in the prediction of this transport associated, partially due to inaccurate predictions of the velocity nonlinearities. The infragravity waves, which coexist with the short waves in the coastal zone, are long-period waves (with 20-200 s) associated to the shortwave groups. Their generation, propagation and dissipation mechanisms are already reasonably well understood, but their in uence on sediment transport is still very poorly characterised. In order to (i) improve current predictions of velocity nonlinearities and (ii) investigate the role of infragravity waves in sediment transport, new experiments were carried out both in a xed-bed wave ume and in a light-weight-sediment wave ume. The physical-modelling data set is used in combination with eld data and numerical simulations for studying both subjects. Existing parameterizations of velocity nonlinearities account only for the in uence of local wave parameters (e.g. wave height, wave length and water depth), which leads to considerable estimation errors, especially of the maximal values of nonlinearity. This work shows that the velocity nonlinearities depend also on non-local wave parameters: (i) o shore wave steepness, (ii) o shore spectral bandwidth and (iii) beach slope. A new parameterization is proposed, which reduces by about 50% the root-mean-square error relatively to former parameterizations. The experimental results in the light-weight-sediment wave ume demonstrate that wave conditions with the same short-wave energy, but di erent low-frequency modulation, shape di erent equilibrium beach pro les. The in uence of the infragravity waves on the sediment transport is con rmed and depends on two di erent mechanisms: (i) advection of the short-wave suspended sediment by the infragravity-waves, which is dependent on the infragravity-wave height and phasing with the short-wave groups and (ii) modulation of short-wave nonlinearities by infragravity-wave motion, both directly and indirectly, through waterdepth modulation. Changes in the beachface morphology induced by infragravity waves are connected to beach-pro le changes in the surf and inner-shoaling zones, highlighting the existent link between the di erent zones of the cross-shore beach pro le.